The role of damaged ship dynamics in addressing the risk of flooding. (1st February 2022) - Vassalos, Dracos
ABSTRACT: Dynamics of damaged ships has repelled close attention until the 1980s, following ground shaking accidents (Herald of Free Enterprise, 1987 and Estonia, 1994). Research since then continues unabated, in the knowledge that damage stability is responsible for 90% of deaths in the maritime industry. Notwithstanding this, safety even in the most advanced maritime nations is still being perceived as unnecessary burden and, as such, it receives attention only as damage reducing exercise. Design for safety and risk-based design have made tremendous inroads in delivering the message that due attention to safety over the life-cycle of the vessel provides the right platform for a cost-effective economic activity whilst serving the higher societal goals. This paper targets to reinforce this belief by providing a methodological treatment of damage ship dynamics whilst addressing the ensuing risk of flooding and offering solutions that have found their way in the maritime industry.